The image of man after September 11 / Mohd. Shaharudin Sabu...[et.al] - Sabu, Mohd. Shaharudin; Supar, Mohd. Saharuddin; Ahmad, Hisammudin; Sulaiman, Shaharin; Abdul Rahim, Ahmad Zuraimi; Bebit, Mohd. Ali Azraei; Mohd Kaulan, Shahrul Munir (2016)
Modern world history had seen March 2003 as the moment of disruption to Islamic civilization in the Middle Eastern region. The American and its ally, Israel’s greed to conquer the oil rich countries in the Middle East has resulted in the death of thousands of innocent victims in Iraq and Palestine regions. Some of the survivors of the war became disillusioned with the war and endured the negative impact on the Muslim society. But they are also others who are optimistic and faced bravely the challenges to survive. Although they have lost their limbs, they still have the strong will power to survive by continuing their previous professions with much difficulty since they now have become handicapped. The researcher’s artwork (cyborg art) is a visual interpretation of the physical shortcomings (handicapped) suffered by the visual artists who continue to survive doing their profession they once held before the war. America has three main reasons for supporting its ally Israel to start war with the Middle – Eastern countries – Iraq and Palestine. First the American greed to conquer the oil rich countries, second to get rid of Saddam Hussein who was powerful in the 1990’s and possessed Weapon of Mass Destruction (WMD) which endangered the security of the Israel people, and thirdly, to introduce American style of democracy which actually the Americans needed to have full political control of all Muslim oil rich countries. Researcher empathize the sufferings of these innocent victims and that he was inspired to produce work to visualize these traumatic experiences.